Islam and the acquisition of knowledge - Ashimi, Tijani Ahmad (World Conference Resources @ WorldConferences.net, Koperasi KOKUIS, Kolej Universiti Islam Antarabangsa Selangor, 2017)
Knowledge is not only learning, but it also encompasses experience. The acquisition of knowledge involves a process of training and education rather than just learning. From the early day of Islam, knowledge has been considered to be the power that has been bestowed upon man in order to qualify him to be the vicegerent of Allah on earth (Khalifatullah). Without knowledge man is not strong enough to fulfill the duties and responsibilities of a vicegerent (Khalifah) to structure his life and his society, as it provides him with values, virtues, visions beliefs and power. Indeed, knowledge in Islamic worldview is a unique gift of the Creator (the most Omniscience and the only Absolute God) to man. As such, it is vital for the success of man in this world and the Hereafter. Furthermore, it is undeniable fact that, knowledge is the root of man’s progress in this transitory world and a crucial factor in his well-being after his demise. Based on the above facts, this humble paper aims to explore vis-a vis the importance of knowledge acquisition in the view of Islam and to disclose the serious attention that Islam has paid toward acquisition of knowledge. However, to achieve the aims and the objectives of this paper, revelation based approach will be applied, that is by referring to the Holy Scripture of Islam (holy Quran) and its perception on knowledge. Finally, the paper will provide a brief conclusion and some recommendations.